Janusian, anomic, agent, and steward: how employees perceive the identity of healthcare organizations - Nunes, F. G.; Martins, L. M. (International Journal of Healthcare Management, 2018)
We suggest that healthcare organizations (HCO) develop a hybrid identity that can be described in a typology made up of four identities: janusian, anomic, agent and steward. These hybrid identity types result from the combination of two seemingly incompatible identities: utilitarian or business oriented versus normative or community care oriented. We also posit that the perception of HCOs’ identity is related with members’ patient-focused behavior and organizational identification. To explore these possibilities, we surveyed a sample of 732 members from three very different HCOs: a non-profit mental health provider, a hemodialysis for-profit company, and a state-owned acute hospital. Results show that our typology of HCOs’ identity discriminates between organizations, between occupations and, more importantly, that patient-focused behaviours and organizational identification are higher when members perceive their organizations as janusian, i.e. rate their organizations high in both utilitarian and normative identities, orientations that do not usually go together. Implications for the management of janusian HCO are discussed.